Pengaruh Citra dan Kepercayaan terhadap Loyalitas Nasabah melalui Kepuasan Nasabah (Management Analysis Journal, 2014)
The purpose of this study is to determine the effect of directly or indirectly image and confidence in the loyalty through customer satisfaction of BRI Unit Sedan, Branch Rembang. The populations in this research are customers of BRI Unit Sedan, Branch Rembang. The number of samples taken in this study were 100 clients by using purposive sampling. Data collection methods used is questionnaires and documentation. Analysis of the data used is descriptive analysis and path analysis. The results of this study indicate that there is the influence of image and trust on customer loyalty through customer satisfaction BRI Unit Sedan, Branch Rembang. The conclusions of this study is the higher the company's image, it will increase satisfaction and loyal ty. And for the trust, the higher the trust, it will increase customer satisfaction and loyalty as well